Bending-hydraulic forming stainless steel thin-walled tube fittings wall thickness distribution law research - Xinlong Zhang; Jiang Xiao; Xiaodong Xie; Zhaosong Jiang; Xueyan Liu (International Journal of Lightweight Materials and Manufacture)
A study was conducted to examine the distribution of wall thickness in stainless steel thin-walled tube fittings during the forming process. The research included simulation and experimental analyses of the bending and hydroforming processes of these fittings used in a passenger car. The goal was to analyze how process parameters affect the distribution of wall thickness. Auto Form software was utilized to simulate the bending process and investigate the impact of relative bending radius (Relative bending radius for the tube fittings bending neutral layer of the ratio of the radius and diameter of the tube) on the wall thickness distribution. Subsequently, hydroforming simulations were performed under varying internal pressure loading conditions. The findings revealed that as the relative bending radius increased, both the maximum thinning rate and maximum thickening rate of the tube fittings gradually decreased. Based on the simulation outcomes, the optimal bending process parameters were determined to be a 62 mm initial tube diameter and a 95 mm bending radius. Through finite element simulations of hydroforming, internal pressures of 30 MPa, 40 MPa, and 50 MPa were compared, with 40 MPa identified as the optimal pressure for forming. The thin-walled tube fittings were then manufactured based on the optimal parameters obtained from the simulation, which were validated through experimentation. The experimental results closely matched the simulation results, with a maximum error margin of 2.27 %. The final formed parts met all requirements without any failures.